Microfacies, geochemistry and sequence stratigraphy of the Sarvak Formation (Mid Cretaceous) in the Kuh-e Siah and Kuh-e Mond, Fars area, southern Iran. (December 2019) - Gholami Zadeh, Parisa; Adabi, Mohammad Hossein; Sadeghi, Abbas
Abstract: During Middle Cretaceous (Late Albian-Early Turonian) period, the Sarvak Formation prevailed in the coastal Fars area (Zagros), southern Iran. This formation is one of the main hydrocarbon reservoirs in the Zagros Basin which has gradually been deposited on the Kazhdomi Formation and unconformably covered by the Laffan shales. This study used thin section descriptions and geochemical analyses to determine the depositional environment of the Sarvak carbonates. Based on the petrographic studies, fifteen microfacies were recognized. These microfacies were deposited in the lagoon, shoal, back reef, reef, fore-reef, shallow open marine and deep open marine facies belts. Facies analysis indicates that the Sarvak limestones were deposited in a carbonate ramp environment which changed to the rimed shelf environment towards the top of the sequence. The minor elements (such as Sr and Mn) and petrographic studies indicate that microfacies could be separated from each other by using trace element values. The aragonite was original carbonate mineralogy These carbonates were affected by the meteoric diagenesis in a semi-closed system. Six transgressive-regressive third-order sequences have been identified. The sequence boundaries have been determined with a sudden change in the depositional and important diagenetic processes related to the relative sea level fall. The maximum flooding surfaces have been recognized by the high value gamma ray log and abundant bioturbation related to the deep facies which separates TST from RST. Graphical abstract: Image 1 Highlights: Fifteen sedimentary facies were recognized. These carbonates were deposited in lagoon, shoal, reef and open marine facies belts. Sarvak Formation was deposited in a ramp to rimmed-platform. The original carbonate mineralogy was aragonite which was affected by meteoric diagenesis in a semi-close system. Sarvak formation was formed in the six sedimentary third-order sequences.